Analysis of the Effect of Job Satisfaction and Organizational Commitment on the Performance of Oe-Cusse Timor Leste Referral Hospital Employees - Corbafo, Jose (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The low performance of the Regional Special Referal Hospital belonging to Oe-Cusse of Timor-Leste illustrates the quality of customer service that affects hospital income. This study aims to analyze the effect of job satisfaction on organizational performance, the effect of commitment on organizational performance, the effect of job satisfaction on organizational commitment, and analyze the most influential variables between job satisfaction and organizational commitment on the organizational performance of Regional Specialty Hospital Referal Oe-Cusse of Timor-Leste. This type of research is a quantitative study using an analytic observational study with a cross-sectional study design. The sample was taken using stratified random sampling so that the sample in this study included medical, nursing, midwifery, and non-medical personnel totaling 130 respondents in Regional Specialty Referal Hospital Oe-Cusse of Timor-Leste. The results showed that there was a relationship between job satisfaction and organization, there was a relationship with organizational performance, there was a relationship between job satisfaction and organizational commitment, and job satisfaction was the variable that most influenced performance (32,10%) compared to organizational commitment (21,90%). Therefore, it is expected that the hospital can maintain and develop the supporting dimensions of job satisfaction and organizational commitment of its employees to achieve organizational performance as expected.